The role of healthcare delivery in the outcome of meningococcal disease in children: case-control study of fatal and non-fatal cases. Issue 7506 (23rd June 2005) - Ninis, Nelly; Phillips, Claire; Bailey, Linda; Pollock, Jon I; Nadel, Simon; Britto, Joseph; Maconochie, Ian; Winrow, Andrew; Coen, Pietro G; Booy, Robert; Levin, Michael
Abstract: Objective To determine whether suboptimal management in hospital could contribute to poor outcome in children admitted with meningococcal disease. Design Case-control study of childhood deaths from meningococcal disease, comparing hospital care in fatal and non-fatal cases. Setting National statistics and hospital records. Subjects All children under 17 years who died from meningococcal disease (cases) matched by age with three survivors (controls) from the same region of the country. Main outcome measures Predefined criteria defined optimal management. A panel of paediatricians blinded to the outcome assessed case records using a standardised form and scored patients for suboptimal management. Results We identified 143 cases and 355 controls. Departures from optimal (per protocol) management occurred more frequently in the fatal cases than in the survivors. Multivariate analysis identified three factors independently associated with an increased risk of death: failure to be looked after by a paediatrician, failure of sufficient supervision of junior staff, and failure of staff to administer adequate inotropes. Failure to recognise complications of the disease was a significant risk factor for death, although not independently of absence of paediatric care (P = 0.002). The odds ratio for death was 8.7 (95% confidence interval 2.3 to 33) with two failures, increasing with multiple failures. Conclusions Suboptimal healthcare delivery significantly reduces the likelihood of survival in children with meningococcal disease. Improved training of medical and nursing staff, adherence to published protocols, and increased supervision by consultants may improve the outcome for these children and also those with other life threatening illnesses.